I am Belfast a city symphony - Holmes, David 1969- (BFI, 2016)
"Beautifully shot by Christopher Doyle and with a powerful soundtrack by the great Northern Irish DJ and composer David Holmes, Cousins' film takes viewers on an emotional journey through the complex and sometimes tragic history of the Northern Irish capital, embodied as a 10,000 year-old woman, compellingly portrayed by Helena Bereen. Interspersing archive material (often detailing the horrors of the Troubles) and newly-filmed footage, "I Am Belfast" is an impassioned and politically engaged love letter to Cousins' hometown." [amazon.co.uk]
Original: Großbritannien 2015
Bildformat 1.78:1
Special features: the making-of "I am Belfast" (Timo Langer, 2015, 14 mins) ; a conversation with Mark Cousins (2015, 14 mins) ; a conversation with Helena Bereen (2015, 11 mins) ; Interview with Christopher Doyle (2015, 10 mins) ; "I am Belfast: a cinematic walk with Mark Cousins" (Takeover Film 2016, 18 mins) ; original trailer; illustrated booklet with new writing by Mark Cousins and Ian Christie, and full film credits
Keywords: Belfast; Film; DVD-Video; Blu-Ray-Disc